Pengaruh Citra Destinasi, Motivasi dan Persepsi Risiko terhadap Kepuasan Wisatawan Sepeda Gunung dan Niat Berkunjung Kembali : di Cacing Fun Track, Lombok Barat - Adinda Marsha Anugrah; Made Antara; Made Sudiana Mahendra (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
Lombok Island has a mountain bike sport tourism destination, namely the Cacing Fun Track which was just inaugurated in 2021. In order for this destination to develop and be able to compete, it is necessary to conduct research on the behavior of sport tourism tourists and the factors that influence the intention to visit again. The purpose of this study was to assess the effect of destination image, motivation and risk perception on tourist satisfaction and intention to return to the Bukit Cacing sport tourism destination (Cacing Fun Track). This research method uses a quantitative approach with a sample of 100 respondents. The sampling technique in this study used purposive sampling and data collection through questionnaires, interviews, observations, and literature studies. The data analysis technique used Structural Equation Modeling (SEM) with the SmartPLS 3.3.5 Student Version analysis tool and was supported by qualitative descriptive analysis techniques. The results showed that the image of the destination had a positive and significant effect on tourist satisfaction and intention to return, tourist motivation had a positive and significant effect on tourist satisfaction and intention to return, risk perception had a negative and significant effect on tourist satisfaction and intention to return, tourist satisfaction had an effect on significant effect on revisit intention and tourist satisfaction had an indirect effect on the influence of destination image, motivation and risk perception towards revisit intention.